Electric energy optimization for the pumps of a cooling and process water system at Södra Cell Värö - Söderström, Emma (My University, 2009)
An investigation of the possibilities for energy optimization in a cooling and process water pumping system at Södra Cell Värö has been performed. This was preceded by an extensive mapping of the system and its users to enhance the knowledge of the network, which resulted in a flow chart. By using the Excel-based computational programme Pumpanalys, the necessary pump head and users limiting in the network could be determined, giving information about the system head curve used for the suggestions for energy optimization. The pump system consists of three old turbo pumps connected in parallel, but normally only one or two pumps are in operation. This project has shown good possibilities to lower the pressure in the concerned water pumping system, provided that the new evaporation plant that will be taken into operation in November this year permits this. By lowering the pressure in the network to below 4.0 bars, operation of one pump should be theoretically possible all year around, provided a maximum volume flow rate demand of 50 000 litres/minute, which has been the mean volume flow rate during the summer months for the past couple of years. With a volume flow rate increase to 60 000 litres/minute, the corresponding maximum pressure is 3.4 bars. In comparison with the operation today, when two pumps operate in parallel more than half the time, this could lead to a power decrease of almost 140 kW. This might however require moderate reconstructions in the system and installation of a booster-pump to the methanol recovery unit. If a further pressure decrease to 3.2 bars in the network is possible, installation of frequency drive on one of the cooling water pumps could be economically feasible. This would lead to a further power decrease of 90 kW. If the pressure demand is even lower, the power demand will also decrease. Together, operating with just one pump at variable speed at 3.2 bars corresponds to a decrease in power demand by 41 %.
Keywords: Kemiteknik; Chemical Engineering